Pembuatan Natrium Karboksimetil Selulosa (Na CMC) Dari Batang Rumput Gajah (Pennisetum purpureum Schumach) - Zulharmitta Zulharmitta; Silvia Maryani; Roslinda Rasyid (Jurnal Farmasi Higea, 2012)
A study on the preparation of sodium carboxymethil cellulose (Na-CMC) from celulose powder that was isolated from the stems elephant grass (Pennisetum purpureum Schumach) has been performed. Cellulose was purified using 17.5% of sodium hydroxide solution, then bleach, dried and crushed to obtain alpha cellulose. Alfa cellulose was eterified with sodium chloroacetat resulting sodium carboxymethyl cellulose, furthermore characterized: organoleptic, losses on drying, chemical identification, pH test and test with fourier transform infrared (FT-IR). The results showed that of 300 g stems elephant grass yield alpha cellulose as much as 92,.54 g and 25 g of alpha cellulose produced  Na-CMC as 16.92 g. Based on the characterization made Na-CMC and Na-CMC Merck®  meet Indonesian Pharmacopoeia 3th edition requirement.